DIFUSI INOVASI PEMBELAJARAN BERBASIS CODING DAN ARTIFICIAL INTELLIGENCE PADA PENDIDIKAN DASAR - Oktarina, Reni; Susanti, Rahmi; Maharani, Siti Dewi; Anwar, Yenny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the diffusion process of innovation in coding- and Artificial Intelligence-based learning in primary education and to identify the factors influencing its implementation. This research employs a qualitative approach using a literature study method. Data were obtained from various scientific sources, including books, national and international journal articles, and educational policy documents relevant to the research topic. Data analysis was conducted through stages of data reduction, data presentation, and conclusion drawing using descriptive qualitative analysis. The results show that the integration of coding in learning can improve students’ computational thinking, creativity, and problem-solving abilities. Meanwhile, the use of Artificial Intelligence enables the development of adaptive and personalized learning systems tailored to students’ learning needs. The diffusion process of technology-based learning innovation in schools occurs through stages of knowledge, persuasion, decision, implementation, and confirmation. The success of implementing this innovation is influenced by several factors, including teachers’ digital competence, the availability of technological infrastructure, and support from educational policies.